2020
DOI: 10.1111/1440-1703.12107
|View full text |Cite
|
Sign up to set email alerts
|

Photographic records of plant phenology and spring river flush timing in a river lowland ecosystem at the taiga–tundra boundary, northeastern Siberia

Abstract: Arctic terrestrial ecosystems near the treeline in river lowlands are vulnerable to the changing climate and seasonal extreme events, including flooding. We set up a simple camera monitoring system to record the timings and durations of the leafy period and the spring flush of river water at three observation sites (Boydom [B]: 70.64°N, 148.15°E; Kodac [K]:70.56°N, 148.26°E; Verkhny‐Khatistakh [VK]:70.25°N,147.47°E) in the Indigirka lowland, in Northeastern Siberia. Time‐lapse digital cameras were located at s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…With reference to previous studies of plant seasons in boreal/arctic ecosystems (e.g., Morozumi et al, 2020;Nagai et al, 2020), we assumed that the definitions of each season varied depending on the latitude of the RWI site. For sites located between 0 and 60 • N, spring was considered to be March, April, and May; summer was June, July, and August; autumn was September, October, and November; and winter was December, January, and February.…”
Section: Response Function Analysismentioning
confidence: 99%
“…With reference to previous studies of plant seasons in boreal/arctic ecosystems (e.g., Morozumi et al, 2020;Nagai et al, 2020), we assumed that the definitions of each season varied depending on the latitude of the RWI site. For sites located between 0 and 60 • N, spring was considered to be March, April, and May; summer was June, July, and August; autumn was September, October, and November; and winter was December, January, and February.…”
Section: Response Function Analysismentioning
confidence: 99%
“…To our knowledge, there are no studies of plant phenology based on ground observations in Siberia; the few existing studies of phenology in this vast area are based primarily on remote sensing data (e.g. Morozumi et al, 2020). These few published studies have reported phenological shifts broadly in line with reports from other ecosystems—including range shifts of forest, tundra, steppe and wetland zones (Meyer et al, 2008; Tchebakova et al, 2010), an extension of the growing season (Shulgina et al, 2011) and increased forest productivity (Berner et al, 2013; Callaghan et al, 2013; Esper & Schweingruber, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, there are no studies of plant phenology based on ground observations in Siberia; the few existing studies of phenology in this vast area are based primarily on remote sensing data (e.g. Morozumi et al, 2020).…”
mentioning
confidence: 99%
“…Flooding commonly occurs during the snowmelt season in Arctic river lowlands (Woo, 2012). The flooding of the Indigirka River mainstream probably extends and contributes to the tributaries, as the water level of the tributary has been observed to suddenly increase even though snow melting had not yet progressed sufficiently in the tributary basin (Morozumi et al, 2020). The same trend of variation in the δ 18 O of the mainstream and tributary until DOY 183 in 2013 (Figure 3) indicates that this contribution of the mainstream water continued until early summer when the flooding had already ended.…”
Section: Discussion Hydrological Processes In the Downstream Region Of The Indigirka Rivermentioning
confidence: 99%